Multicolour single molecule imaging in cells with near infra-red dyes. - Christopher J Tynan; David T Clarke; Benjamin C Coles; Daniel J Rolfe; Marisa L Martin-Fernandez; Stephen E D Webb (PLoS ONE)
Background The autofluorescence background of biological samples impedes the detection of single molecules when imaging. The most common method of reducing the background is to use evanescent field excitation, which is incompatible with imaging beyond the surface of biological samples. An alternative would be to use probes that can be excited in the near infra-red region of the spectrum, where autofluorescence is low. Such probes could also increase the number of labels that can be imaged in multicolour single molecule microscopes. Despite being widely used in ensemble imaging, there is a currently a shortage of information available for selecting appropriate commercial near infra-red dyes for single molecule work. It is therefore important to characterise available near infra-red dyes relevant to multicolour single molecule imaging. Methodology/principal findings A range of commercially available near infra-red dyes compatible with multi-colour imaging was screened to find the brightest and most photostable candidates. Image series of immobilised samples of the brightest dyes (Alexa 700, IRDye 700DX, Alexa 790 and IRDye 800CW) were analysed to obtain the mean intensity of single dye molecules, their photobleaching rates and long period blinking kinetics. Using the optimum dye pair, we have demonstrated for the first time widefield, multi-colour, near infra-red single molecule imaging using a supercontinuum light source in MCF-7 cells. Conclusions/significance We have demonstrated that near infra-red dyes can be used to avoid autofluorescence background in samples where restricting the illumination volume of visible light fails or is inappropriate. We have also shown that supercontinuum sources are suited to single molecule multicolour imaging throughout the 470-1000 nm range. Our measurements of near infra-red dye properties will enable others to select optimal dyes for single molecule imaging.